Internacionalização da educação superior nos marcos da integração regional da América Latina – o caso da Universidade Federal da Integração Latino-Americana - Eduardo Santos (EccoS – Revista Científica)
Especially since the emergence of the processes of market integration (globalization) and cultures (globalization), which marks the contemporary world economic and political order, the efforts of academic communities, policymakers and national governments of the Latin American countries combine in the direction of reconfiguring their higher education systems and policies based on one word: internationalization. In this scenario, there is a dialectic that tends to confront (not necessarily oppose) the local/national historical demands of inclusion and professionalization of citizenship, by definition referred to the Nation-State, to the imperatives of a geopolitics of knowledge commanded by dynamic centers of capitalism, which in turn are based on a defined (and prestigious) model of higher education, the world class universities, according to criteria pointed out and measured by international rankings, thus characterizing a process of transnationalization rather than internationalization. In this work, we identify the most classic forms of internationalization historically adopted by Latin American higher education systems and policies, and then analyze the institutional response offered to internationalization requirements with the recent implementation of a Brazilian federal university: the University of Latin-American Integration (Unila), highlighting its strong relationship with the Brazilian foreign policy of regional integration for the territory covered by Mercosur. We defend the understanding that Unila is guided by institutional, curricular and epistemological conceptions that are alternatives to hegemonic models and that potentially represent a vision of higher education policy that seeks another configuration for the geopolitics of knowledge in Latin American space. This work presents preliminary analyzes of the researches (bibliographical, documentary and field) carried out under the project “Observatory of the Popular University in Brazil”, developed by the Postgraduate Program in Education of the University of Nove de Julho (PPGE-Uninove), with support from Capes.